Bahasa, Simbol, Dan Makna: Analisis Antropologi Budaya Dalam Komunikasi Masyarakat - Yeti Novia (CV. SINAR HOWUHOWU, 2025)
Communication is often narrowly conceived as a mere process of information exchange. Departing from this perspective, this article argues that communication is a fundamental cultural practice through which social reality is constructed and negotiated. Through the lens of cultural anthropology, this study aims to analyze the inextricable link between language, symbols, and meaning within a community. The study employs a qualitative approach, using ethnographic methods among the Dayak ‘Sungai Emas’ Indigenous community in Kalimantan (Borneo). The findings reveal three main points: first, the existence of 'tutur bertuah' (efficacious speech), where language in ritual contexts functions performatively to create reality; second, ritual symbols possess multivocal properties, condensing complex social and cosmological meanings; and third, meaning is dynamic and actively negotiated through communicative competence in social practices such as musyawarah adat (customary deliberation). This study concludes that language and symbols are not merely tools for communication but are the very foundation of a society's social order and worldview. This analysis underscores the importance of an interpretive approach to deeply understand the diversity of human communicative practices.